Chromium disrupts chromatin organization and CTCF access to its cognate sites in promoters of differentially expressed genes. Issue 4 (3rd April 2018) - VonHandorf, Andrew; Sánchez-Martín, Francisco Javier; Biesiada, Jacek; Zhang, Hongxia; Zhang, Xiang; Medvedovic, Mario; Puga, Alvaro
ABSTRACT: Hexavalent chromium compounds are well-established respiratory carcinogens used in industrial processes. While inhalation exposure constitutes an occupational risk affecting mostly chromium workers, environmental exposure from drinking water is a widespread gastrointestinal cancer risk, affecting millions of people throughout the world. Cr(VI) is genotoxic, forming protein-Cr-DNA adducts and silencing tumor suppressor genes, but its mechanism of action at the molecular level is poorly understood. Our prior work using FAIRE showed that Cr(VI) disrupted the binding of transcription factors CTCF and AP-1 to their cognate chromatin sites. Here, we used two complementary approaches to test the hypothesis that chromium perturbs chromatin organization and dynamics. DANPOS2 analyses of MNase-seq data identified several chromatin alterations induced by Cr(VI) affecting nucleosome architecture, including occupancy changes at specific genome locations; position shifts of 10 nucleotides or more; and changes in position amplitude or fuzziness . ATAC-seq analysis revealed that Cr(VI) disrupted the accessibility of chromatin regions enriched for CTCF and AP-1 binding motifs, with a significant co-occurrence of binding sites for both factors in the same region. Cr(VI)-enriched CTCF sites were confirmed by ChIP-seq and found to correlate with evolutionarily conserved sites occupied by CTCF in vivo, as determined by comparison with ENCODE-validated CTCF datasets from mouse liver. In addition, more than 30% of the Cr(VI)-enriched CTCF sites were located in promoters of genes differentially expressed from chromium treatment. Our results support the conclusion that Cr(VI) exposure promotes broad changes in chromatin accessibility and suggest that the subsequent effects on transcription regulation may result from disruption of CTCF binding and nucleosome spacing, implicating transcription regulatory mechanisms as primary Cr(VI) targets.